GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU PADA SDN 7 MUARA DUA LHOKSUEMAWE - Zuryati .; Djailani AR; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Style principals strongly influence the behavior of subordinates, but if subordinate behavior may not necessarily be able to influence the behavior of their superiors. Principal's leadership style is a consistent pattern of behavior shown by the leader and the other party known as a leader trying to influence the activities of others. The purpose of the study to determine the leadership style of the principal, including: (1) Discipline; (2) Commitment; (3) Ability and (4) The responsibility of the teacher. Qualitative approach with descriptive methods, data collection techniques performed with interview guides, observation, and study documentation. Subjects were principals, teachers and supervisors in SD Negeri 7 Muara Dua Lhoksuemawe. The results of the study found: (1) the principal's style of leadership in promoting the discipline of teachers, is a style of informing (telling), in addition to telling style, principals also apply situational style; (2) the principal's leadership style in improving teacher commitment is selling styles (consultative) by directing the teacher to complete the task; (3) the principal's leadership style to improve the ability of teachers, namely the implementation of a participative style during an internal meeting board of teachers and other meetings; and (4) the principal's style of leadership in improving the teacher's responsibility, is to force the sharing discretionary authority to the members of the organization to carry out the task. Expected to supervisors and principals in order to give impetus and direction in the performance of discipline, commitment, ability and responsibility of teachers to effectively and efficiently to improve the performance of teachers in schools.Keywords: Principal Leadership Styles and Teacher PerformanceAbstrak: Gaya kepala sekolah sangat mempengaruhi perilaku bawahannya, tetapi bila perilaku bawahan belum tentu dapat mempengaruhi perilaku atasannya. Gaya kepemimpinan kepala sekolah adalah suatu pola perilaku konsisten yang ditunjukkan oleh pemimpin dan diketahui pihak lain ketika pemimpin berusaha memengaruhi kegiatan orang lain. Tujuan penelitian untuk mengetahui gaya kepemimpinan kepala sekolah, meliputi: (1) Disiplin; (2) Komitmen; (3) Kemampuan dan (4) Tanggung jawab guru. Pendekatan kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan dengan pedoman wawancara, pedoman observasi, dan studi dokumentasi. Subjek penelitian adalah kepala sekolah, guru dan pengawas di SD Negeri 7 Muara Dua Lhoksuemawe. Hasil penelitian ditemukan: (1) Gaya kepemimpinan kepala sekolah dalam meningkatkan disiplin guru, adalah gaya memberitahukan (telling), selain gaya telling, kepala sekolah juga menerapkan gaya situasional; (2) Gaya kepemimpinan kepala sekolah dalam meningkatkan komitmen guru adalah gaya selling (konsultatif) dengan mengarahkan guru untuk menyelesaikan tugasnya; (3) Gaya kepemimpinan kepala sekolah dalam meningkatkan kemampuan guru, yaitu gaya partisipatif yang diterapkannya pada saat rapat internal dewan guru dan rapat lainnya; dan (4) Gaya kepemimpinan kepala sekolah dalam meningkatkan tanggung jawab guru, ialah gaya delegatif yaitu melakukan sharing authority kepada anggota untuk melaksanakan tugas organisasi. Diharapkan kepada pengawas dan kepala sekolah supaya dapat memberikan dorongan dan arahan dalam kerja tentang disiplin, komitmen, kemampuan dan tanggungjawab guru secara efektif dan efesien untuk meningkatkan kerja di sekolah.Kata Kunci: Gaya Kepemimpinan Kepala Sekolah dan Kinerja Guru